2006
DOI: 10.1007/s11199-006-9124-x
|View full text |Cite
|
Sign up to set email alerts
|

College Men, Their Magazines, and Sex

Abstract: Relations between reading Lad magazines and pornographic magazines and the beliefs and attitudes that are consistent with their content were explored in two independent surveys of college undergraduate men (n=91 and 68, respectively). The impact of reading such magazines on men's sexual self-schema was also examined. The results indicated a relationship between reading Lad magazines and endorsement of permissive sexual attitudes independent of actual sexual behavior. Reading Lad magazines was also associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 23 publications
1
38
1
2
Order By: Relevance
“…The present research broadly contributes to the debate about the influence of women's sexualization in the media on the attitudes and behavioral tendencies of men (Horvath et al, 2012;Krassas et al, 2003;Peter & Valkenburg, 2007;Taylor, 2005Taylor, , 2006. Data obtained showed a significant relationship (in the expected direction)…”
Section: Discussionsupporting
confidence: 52%
“…The present research broadly contributes to the debate about the influence of women's sexualization in the media on the attitudes and behavioral tendencies of men (Horvath et al, 2012;Krassas et al, 2003;Peter & Valkenburg, 2007;Taylor, 2005Taylor, , 2006. Data obtained showed a significant relationship (in the expected direction)…”
Section: Discussionsupporting
confidence: 52%
“…Approximately one in five men indicated at least some weekly reading. Asking about specific magazines has been normative in past magazine and sexual socialization research (Peter & Valkenburg, 2007;Taylor, 2006). Maxim and Esquire were used as the particular referents because of their popularity and because the objectification of women in these periodicals has been noted by several Arch Sex Behav scholars (Brunner, 2013;Johnson & Sivek, 2009;Krassas et al, 2003;Reichert, 2007;Taylor, 2005).…”
Section: Men's Magazine Exposurementioning
confidence: 99%
“…For example, Taylor (2006) found that reading both semi-explicit and explicit magazines was associated with more permissive attitudes towards premarital sexual activity and expectations of variety for both usual and unusual sexual behaviors among college men. SEM use has also been associated with lowered sexual anxiety and more positive sexual esteem (Morrison, Harriman, Morrison, Bearden, & Ellis, 2004).…”
Section: Sem Use and Sexual Behaviors Satisfaction And Preferencesmentioning
confidence: 99%
“…It was anticipated that SEM viewing frequency would be associated with more and earlier sexual experience (Carroll et al, 2008), less sexual and relationship satisfaction (Peter & Valkenburg, 2009) and more varied or unusual sexual preferences (Taylor, 2006). Though no past research has examined the role of viewing multiple types of SEM, it was anticipated that it will have similar outcomes as SEM viewing frequency.…”
Section: Current Studymentioning
confidence: 99%